EFIKASI TAMSULOSIN PADA BENIGN PROSTATIC HYPERPLASIA DENGAN RETENSIO URINE AKUT YANG MENJALANI TRIAL WITHOUT CATHETER - Kholis, Khoirul; Soetojo, Soetojo; Djojodimedjo, Tarmono; P, Widodo J (Indonesian Journal of Urology, 2009)
Objective: To evaluate the efficacy of tamsulosin on BPH patients with acute urinary retention on trial without catheter (TWOC). Materials & method: This study was a post test only-placebo group design comparing residual urine in BPH patients with acute urinary retention on TWOC between groups administered with tamsulosin and placebo. The efficacy of both groups with tamsulosin and placebo on the 3rd and 14th day was analyzed using Chi Square test while the efficacy of administration of tamsulosin and placebo on the 3rd and 14th day was analized using Mc Nemar test. Results: This study showed that there was still urinary retention in 7 patients (58,3%) and 4 patients (44,4%) shared recovery within 3 days of tamsulosin administration, while 5 patients (41,7%) still had urinary retention compared to 5 patients (55,6%) who showed recovery in the placebo group. The difference was insignificant with p=0,670. Patients who dropped out from TWOC on the 3rd day and given tamsulosin until the 14th day showed urinary retention in 4 patients (44,4%) and recovery in 3 patients (100%) while all samples who were given placebo showed urinary retention 5 patients (55,6%). The difference was insignificant with p=0,205. Follow up for 3 days in Tamsulosin groups which have urine retention in this study, 3 patients became free for urine retention and the other 4 patients still had urine retention. But in this study, no difference in efficacy with p=1,025. In placebo groups with urinary retention before the 3rd day of administration still showed urinary retention after the 14th day. Conclusion: There was no statistical differences on the success of TWOC, between groups administered with 0,2 mg of tamsulosin and placebo group, neither on the 3rd day nor on the 14th day. There was reduction of recatheterization because of failure of TWOC with patients who were given tamsulosin for 14 days.